Transformations of Diatom-Derived Dissolved Organic Matter by Bacillus pumilus Under Warming and Acidification Conditions - Liu, Yang; Wang, Xueru; Sun, Jun (Frontiers in Microbiology, 2022)
Have you provided each of the Reviewers with details of the changes in your revised manuscript? Reviewers sometimes fail to notice improvements that aren't pointed out. All comments you have entered on the Reviewer tabs will be submitted to the Reviewers together with your revised manuscript. If there are no Reviewers tabs, please provide the details in the Editor/AE tab. Are you satisfied with your responses in the discussion forum and would you like to proceed with re-submission?